2023
DOI: 10.3390/horticulturae9080947
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Structural Changes in Apple Tree Branches of Different Varieties during Dormancy

Gongxun Xu,
Meiqi He,
Deying Zhao
et al.

Abstract: Low temperature is an abiotic stress factor limiting the distribution of fruit tree cultivation areas. As temperate deciduous fruit trees, apple (Malus domestica) trees go dormant in the winter to adapt to or avoid damage caused by low temperatures. The capacity for cold resistance is closely linked to the physiological, biochemical, and structural characteristics of one-year-old branches. In this study, we investigated such changes in the branches of cold-resistant ‘Hanfu’ (HF) and cold-sensitive ‘Naganofuji … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
5
1
Order By: Relevance
“…Cold-resistant resources notably have a more defined phellem layer and a higher degree of phellem transformation, consistent with findings from walnut branch research [ 69 ]. The phloem thickness of Kanoiwa was significantly higher than that of other varieties in this study; however, its cold resistance was found to be low (LR) in the comprehensive evaluation, which contradicts previous findings on the cold resistance of raspberry [ 67 ] and apple [ 70 ]. Anatomical features can provide considerable insight into a plant’s cold resistance, offering valuable comparative measures for different resources.…”
Section: Discussioncontrasting
confidence: 99%
“…Cold-resistant resources notably have a more defined phellem layer and a higher degree of phellem transformation, consistent with findings from walnut branch research [ 69 ]. The phloem thickness of Kanoiwa was significantly higher than that of other varieties in this study; however, its cold resistance was found to be low (LR) in the comprehensive evaluation, which contradicts previous findings on the cold resistance of raspberry [ 67 ] and apple [ 70 ]. Anatomical features can provide considerable insight into a plant’s cold resistance, offering valuable comparative measures for different resources.…”
Section: Discussioncontrasting
confidence: 99%
“…Proline content was determined using the sulfosalicylic acid-acid ninhydrin method, as described by He et al [ 55 ]. The soluble protein content was determined by Coomassie brilliant blue staining according to the method described by Xu et al [ 3 ]. The soluble sugar content was determined by anthrone colorimetry according to the method described by Xu et al [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, due to climate change, the growing season is prolonged, the vegetative growth of apples is vigorous, new shoots stop growing late, and low-temperature exercise is insufficient. Under extreme weather conditions with rapid cooling, immature branches are vulnerable to freeze-drying and death, which affect reproductive growth [ 3 ]. Therefore, it is important to improve the freezing resistance of apples during dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…The soluble protein (SP) content and the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) were determined according to the method of Liu et al [4], Shi et al [18], and Xu et al [8]. For the SP, SOD, POD, CAT, and APX detection, approximately 0.1 g of the leaf samples was taken into a mortar, and 1 mL ice-cold sodium phosphate-buffered solution (50 mmol L −1 , pH 7.0) mixed with ethylenediaminetetraacetic acid (1.0 mmol L −1 ) and 2% polyvinylpyrrolidone was added in an ice bath.…”
Section: Determination Of Leaf Physiological Changesmentioning
confidence: 99%
“…Temperature, one of the primary factors affecting plants, can induce altitudinal and latitudinal differentiation in plant populations [5,6]. It is well known that cold stress obviously changes the morphological structure and physiological and metabolic characteristics of plants, and that leaves are the most affected organ [7,8]. For example, plants growing in regions with lower temperatures often have a thicker cuticle (CT) layer, a decreased proportion of spongy tissue (ST), and an increased proportion of palisade tissue (PT) in their leaves [9].…”
Section: Introductionmentioning
confidence: 99%